2004
DOI: 10.1063/1.1650298
|View full text |Cite
|
Sign up to set email alerts
|

The elementary steps of the photodissociation and recombination reactions of iodine molecules enclosed in cages and channels of zeolite crystals: A femtosecond time-resolved study of the geometry effect

Abstract: We present femtosecond time-resolved pump-probe experiments on iodine molecules enclosed into well-defined cages and channels of different crystalline SiO2 modifications of zeolites. The new experimental results obtained from iodine in TON (Silica-ZSM-22), FER (Silica-Ferrierit), and MFI (Silicalit-1) porosils are compared with data published earlier on the iodine/DDR (Decadodecasil 3R) porosil system [Flachenecker et al., Phys. Chem. Chem. Phys. 5, 865 (2003)]. A summary of all findings is given. The processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The increase in emission intensity in the presence of CDs is explained in terms of increase of trans-AZO population upon encapsulation and restriction in motion of caged and photoproduced HYZ structure. However, 13 C-T 1 measurements have shown that for some populations of OII:␤-CD complexes, the guest molecule still can move within the cavity (26,27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in emission intensity in the presence of CDs is explained in terms of increase of trans-AZO population upon encapsulation and restriction in motion of caged and photoproduced HYZ structure. However, 13 C-T 1 measurements have shown that for some populations of OII:␤-CD complexes, the guest molecule still can move within the cavity (26,27).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion complexes of OII and CDs have been studied by several groups showing the formation of a 1:1 entity (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). So far, the CD inclusion complex studies have considered that OII in water solutions exists under AZO tautomer, contrary to many studies in solutions where OII coexists under AZO and HYZ forms (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Recently, ultrafast transient lens technique with a response function of Ϸ300 fs has been used to study the dynamics of OII in CD (36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental relevance of toxic gas capture and the electric conductivity enhancement caused by iodine uptake, have raised great interest on the incorporation of dihalogen molecules in diverse hosts like clathrasils,, zeosils,, and ALPOs, but also organic salts, organic zeolites, Hofmann clathrates,, and other MOFs …”
Section: Organization Of Dihalogens In 1d Channelsmentioning
confidence: 99%
“…In this study, a hole-type conducting semiconductor iodine was used as the guest substance. It is often considered as the model object when creating and studying various nanostructures in solid-state physics [5][6][7][8][9][10][11][12][13][14][15] and has prospects for practical application in electronics [16], photonics [17], and medicine [18] (where zeolite matrices can be used for targeted drug delivery [19]).…”
Section: Introductionmentioning
confidence: 99%